Perbandingan tahap pengetahuan, sikap dan kesan dadah dalam kalangan remaja sekolah berisiko - Norhayati Ibrahim,; Rozmi Ismail,; Noh Amit,; Noordeyana Tambi,; Mohd Nasir Selamat,; Muhammad Ajib Abd Razak,; Nor Azri Ahmad,; Nurul Shafini Shafurdin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The phenomenon of adolescents involved with drug abuse is a worrying and very serious issue. The influence of drug-related partners would have a bad effect on other teens, especially teenagers who are at risk. Therefore, this study aims to identify the extent of the level of knowledge of the drug, especially in relation to the differences of attitudes in terms of physical effects, hindering behaviors, involvement in drug-related activities and information on how to distribute, attitude towards self and future, and risk factors amongst students who did take drugs as compared to who never took it. This is a cross-sectional study involving 559 teenagers at risk, aged between 13-18 years’ old who are involved in SHIELDS Programme, camp based programme that was introduced by Agensi Anti dadah Kebangsaan (AADK) in collabaration with the Ministy of Education. Findings showed that there is a significant difference between students who have taken drugs and those who have never used it for dimension of hindering behavior, involvement in drug-related activities and information on how to distribute, risk factors of the involvement of immediate family members with drugs and negative consequences of drug intake. Because the involvement with drugs negatively impacts adolescents, thus, the prevention of this deviance behavior must be implemented as best as possible to ensure that the future of these adolescents is upheld, to prevent them from falling into another crime.